2015
DOI: 10.1111/jgh.12683
|View full text |Cite
|
Sign up to set email alerts
|

Response evaluation with endoscopic ultrasound and computed tomography in esophageal squamous cell carcinoma treated by definitive chemoradiotherapy

Abstract: Response evaluation by miniprobe endoscopic ultrasound and computed tomography can predict the prognosis of esophageal squamous cell carcinoma patients treated by definitive chemoradiotherapy. Those who were judged as poor responder should receive additional treatment to improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…After completion of 36-gray radiotherapy, a EUS exam was conducted to assess the treatment response. [ 11 ] Briefly, the esophageal mucosa and intraluminal lesion were first inspected by general upper gastrointestinal scope. Then, a EUS miniprobe (2.5 mm in diameter) was inserted into esophageal lumen via the working channel to scan the previous tumor area.…”
Section: Methodsmentioning
confidence: 99%
“…After completion of 36-gray radiotherapy, a EUS exam was conducted to assess the treatment response. [ 11 ] Briefly, the esophageal mucosa and intraluminal lesion were first inspected by general upper gastrointestinal scope. Then, a EUS miniprobe (2.5 mm in diameter) was inserted into esophageal lumen via the working channel to scan the previous tumor area.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that high miR-193a-5p was correlated with a good CCRT response in KYSE170 and KYSE70 cells. ESCC patients who received CCRT treatment were grouped into good or poor CCRT responses according to the criteria described in a previous study [24, 25]. To verify whether miR-193a-5p is a potential biomarker for the CCRT response, five CCRT good response and four CCRT poor response patient RNA samples were used to evaluate miR-193a-5p expression by real-time PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analysis revealed that chemotherapy regimen and RR were strongly related to survival, and this is consistent with the results of previous researches. 19 , 27 A study reported by Chang et al 19 demonstrated that treatment response is the strongest independent prognostic factor of survival. A previous randomized Phase III clinical trial showed that patients with the higher RR had longer survival than those with lower RR, suggesting that RR might closely be related to longer survival.…”
Section: Discussionmentioning
confidence: 99%
“…The chemotherapy regimen greatly affected the CR and RR, which has been proven to be independent prognostic factors for survival. 18 , 19 To our knowledge, the cisplatinum/paclitaxel regimen has never been compared with the cisplatinum/5-FU regimen directly, for patients with locally advanced ESCC who are not receiving curative intended surgery. Therefore, the optimal chemotherapy regimen is debatable.…”
Section: Discussionmentioning
confidence: 99%